Case study: Design Parameter Analysis for a Hydraulic Modeling of a Floodplain Protection of La Estrella River, Limón, Costa Rica - Watson, Fernando (2020)
In the basin of La Estrella River, deforestation in the upper and lower parts of the river has weakened the capacity for material retention of the basin, increasing the frequency and destructive capacity of extreme discharges. Additionally, the Limon earthquake of 1991 caused geological disturbance, especially in La Estrella Valley, modifying the traditional dynamics and stability of its river channel. Specifically, one river section which is the object of this study shows two aggravating circumstances: a human settlement and the location of the only access road to that settlement very near the river channel, implying higher risk for the settlement and the need to implement protection works. We have therefore compared the results of hydraulic 1D and 2D models to demonstrate the importance of information and its analysis for making decisions about the design of these protection and mitigation works in the river.